Ob stoletnici rojstva akademika Dragotina Cvetka (1911-1993) = At the Hundredth Birth Anniversary of Dragotin Cvetko (1911-1993), Member of the Slovenian Academy of Sciences and Arts - Kokole, Metoda; Zupančič, Maruša (ZRC SAZU, Založba ZRC, 2012)
The present book is volume of conference proceedings of the scientific meeting dedicated to the founder of modern Slovenian musicology, Dragotin Cvetko, and organised by the Institute of Musicology of the Scientific Research Centre of the Slovenian Academy of Sciences and Arts with the financial support of the Slovenian Research Agency and the Slovenian Academy of Sciences and Arts. The papers, organised in four linked and intertwining subject sections (Dragotin Cvetko - life and work~Metamorphoses of national music historiographies~European music historiographies - selected chapters~and Musicology - from national towards global) are accompanied in the present volume by some basic facts on Dragotin Cvetko, whose life and works it celebrates, and four addresses in his honour. The book is rounded off by a list of master and doctoral theses supervised by Professor Cvetko and a chronological presentation of events that celebrated in September 2011 the hundredth anniversary of his birth.